Algebraic and analytic methods in representation theory - Orsted, Bent; Schlichtkrull, Henrik, 1954- (Perspectives in mathematics, 1997)
This book is a compilation of several works from well-recognized figures in the field of Representation Theory. The presentation of the topic is unique in offering several different points of view, which should makethe book very useful to students and experts alike. Presents several different points of view on key topics in representation theory, from internationally known experts in the field.